Effects of food nutrition labels on the health awareness of school-age children - Ching-Yi Wang; Chung-Jia Hsu; Dengchuan Cai (BMC, 2022)
Abstract Background Overweight and obesity have been described as a global epidemic that seriously affects the health of adults and children. Front of Package (FOP) Nutrition Labeling can increase consumers' awareness of unhealthy foods. The purpose of this study is to find effective deterrence and improve children's health awareness via the FOP. Methods This study examined children's health awareness of snack packaging using the four labels: guideline daily amounts (GDA), traffic light system (TLS), Apple label (designed in this study), and Warning label. This study recruited 343 children in the sixth grade, including 223 children living in cities and 120 children living in rural areas. First, 30 children in grades 3 to 6 selected 8 snacks that they often buy. Then, each snack was synthesized into these four labels according to their nutritional content for a total of 32 samples. Finally, a questionnaire was used to evaluate the health of snack packaging and the visibility of nutrition labels. Results Four results can be drawn: (1) GDA, Apple label and TLS can help children determine healthier snack choices, (2) black Warning label cannot induce children to make healthier choices, (3) children who often buy snacks have low health awareness, and (4) rural children have weak health awareness of snack packaging. Conclusions These results can provide a packaging label design, which can effectively improve children's health awareness.